Towards a Categorization of Instrumental Timbres for Analytical and Creative Purposes - Cordero, Victor; Soden, Kit (Circuit)

(untitled) (Circuit, musiques contemporaines, 2025)
This article presents a framework for classifying instrumental timbres, addressing the expanding sonic possibilities in contemporary orchestration and musical practice. As composers move beyond pitch-centered traditions, integrating noise-based effects and extended techniques—new analytical tools become necessary. This study introduces the concepts of metatimbre and paratimbre, structuring and applying them through Metatimbre Classes (MetCs) to categorize timbres based on perceptual similarity rather than instrumental origin or technique. MetCs encompass single-instrument, multi-instrument, or hybrid sources, grouping timbres under musical archetypes such as “flute-like” or “breath-like.” Analyses of György Ligeti’s Kammerkonzert and Helmut Lachenmann’s temA illustrate the framework’s applicability. By shifting the focus from individual instruments and their techniques to broader timbral groupings, this framework provides a structured approach for analyzing and conceptualizing timbre and its functional role in orchestration.